First report on interferon related developmental regulator-1 from Macrobrachium rosenbergii: bioinformatic analysis and gene expression - Arockiaraj, J.; Easwvaran, S.; Vanaraja, P.; Singh, A.; Othman, R.Y.; Bhassu, S. (Elsevier, 2012)
This study reports the first full length gene of interferon related developmental regulator-1 (designated as MrIRDR-1), identified from the transcriptome of Macrobrachium rosenbergii. The complete gene sequence of the MrIRDR-1 is 2459 base pair long with an open reading frame of 1308 base pairs and encoding a predicted protein of 436 amino acids with a calculated molecular mass of 48 kDa. The MrIRDR-1 protein contains a long interferon related developmental regulator super family domain between 30 and 330. The mRNA expressions of MrIRDR-1 in healthy and the infectious hypodermal and hematopoietic necrosis virus (IHHNV) infected M. rosenbergii were examined using qRT-PCR. The MrIRDR-1 is highly expressed in hepatopancreas along with all other tissues (walking leg, gills, muscle, haemocyte, pleopods, brain, stomach, intestine and eye stalk). After IHHNV infection, the expression is highly upregulated in hepatopancreas. This result indicates an important role of MrIRDR-1 in prawn defense system.